Judging By The Methodology Of Learning Islamic Education Which Eroded The Times - Ainun Mardia Harahap (International Journal Of Humanities Education and Social Sciences (IJHESS), 2021)
Learning methodology is part of the set of scientific disciplines that become its parent. Almost all sciences have their own methodologies. Therefore, Islamic education as one of the disciplines has a methodology, namely the method of Islamic education. Islamic education from year to year resulted in many changes in the Islamic world. Both in terms of religion, education, politics and so on. Especially in the field of Islamic education, due to the attitude of the educators who are permissive and indulgent, many children fall into associations that ignore the Shari'ah. Many educators forget their nature as uswahnya students who are obliged to educate students to have good morals. This results in the child's world being in vain. Giving quite a lot of contribution to the futility of the western educational methods that seem to have become the mecca of our education. So that every educator uses more general education methods, even the methods used in their learning programs are by using the lecture method, question and answer, discussion, demonstrators, and so on. This naturally erodes the understanding of educators and students on Islamic education methods. Actually Islam has a perfect education method for mankind, especially in the field of Islamic education. Therefore, educators return to their hittah, namely mastering Islamic education methods, so that the function of Islamic Education Methods will later help realize and carry out the goals of education it self.